Understanding dramaturgic theory as the key to choosing an ideal leader - Sabaruddin, Sabaruddin; Agustan, Agustan; Ibrahim, Intan Soliha; Rahman, Saifur; Maharani, Maharani (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2024)
The concept of dramaturgy focuses on social life as a dramatic performance with the strategy of creating an appealing image for the public. The purpose of this research is to examine the roles and challenges of using dramaturgy in selecting an ideal leader. This research uses qualitative methods. Informants in this study consist of community figures, traditional leaders, and legislative candidates in Mancani Village. Data collection through observation, interviews, and documentation. Data analysis techniques applied include data collection, data reduction, data presentation, and conclusion. The results show that dramaturgy in leadership selection can reveal aspects of leaders that may not be apparent through their vision and mission, build attractiveness towards leaders in the eyes of the public, and effectively package political messages to create a convincing image. However, challenges in implementing dramaturgy include maintaining the authentic identity of a leader, difficulty in distinguishing between genuine character and constructed imagery, and diverse expectations from the community towards their leaders. Therefore, leaders must maintain their integrity and authentic identity in fulfilling their leadership roles. This helps them meet the expectations of the people they lead and maintain the trust that has been established.